Hubungan Terpaan Tweet “Twitter, Please Do Your Magic” dengan Sikap Remaja - Alya Ratna Dewi; Dadi Ahmadi (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Twitter as microblogging is a popular form of short blog offers a variety of new information quickly through short messages that someone shares through the timeline. The appearance of the phrase